Effectiveness of cervical stabilisation training and correction of muscle imbalance, following reduction of atlanto-axial rotatory subluxation: A single case study - Debbie Davidson (AOSIS, 1998)
Atlanto-axial rotatory subluxation is a rare, controversial and frequently misdiagnosed condition occurring primarily in children. A single case study design was used to evaluate the effectiveness of cervical stabilisation training and correction of muscle imbalance, following reduction of this condition, in a nine-year-old boy. The study was conducted over a six-week period during which the subject maintained a daily diary to record his symptoms. The programme consisted of various muscle relaxation and lengthening techniques, endurance training of the deep cervical flexors and lower scapular stabilisers, as well as postural re-education. No treatment was directed at the articular component. The patients signs and symptoms were greatly reduced during the study period. This study supports the importance of correcting the muscle dysfunction component in cervicogenic pain sufferers.